The power of woke and other forms of disproportionate punishment - Lars Gårn Hansen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2023)
I suggest that simple enforcement and lobbying models may explain how a small minority of dedicated believers (religious fundamentalists, animal rights activists, woke activists, etc.) are able to impose changes in behavior on the majority in a society who do not believe. With this, a society typically has two stable states: one with and one without the majority changing behavior. I show how activists can facilitate transition to their preferred state by focusing punishment on subsets of the behavior they want to change and on subgroups of the majority one at a time, as well as by exploiting inherent advantages they have in lobbying the leadership of subgroups with power hierarchies (corporations, universities, organizations, etc.). The willingness of dedicated believers to inflict highly disproportionate punishment on members of the majority turns out to be critical for their ability to facilitate transition. I show that transition to the state in which the majority changes behavior may substantially reduce social welfare. I conclude with a discussion of strategies for avoiding transition, which the majority may consider.
Keywords: D0; D7; H0; P4; L51; 330; woke activism; private enforcement; lobbying